The ‘Ibero-American Geographical Atlas’ of the Barcelona publishing house Alberto Martín (1901-1915) - Montaner, Carme (2023)
Alberto Martín was a publishing house founded in Barcelona in 1895 and specialized in the publication of geographical books. One of his most outstanding projects was the publication of a collection of Ibero-American geographical atlases. From 1901 began to publish the atlas of Spain in fascicles and later of Portugal, Peru and Mexico would come. The project had no continuation, probably due to marketing problems, despite having an outstanding cartography drawn up under the direction of Benito Chías Carbó. Well known in Spain, the Ibero-American geographical atlas project is practically unknown in Latin America.